Infant attention to rhythmic audiovisual synchrony is modulated by stimulus properties - Cirelli, Laura K.; Talukder, Labeeb S.; Kragness, Haley E. (Frontiers in Psychology, 2024)
Musical interactions are a common and multimodal part of an infant’s daily experiences. Infants hear their parents sing while watching their lips move and see their older siblings dance along to music playing over the radio. Here, we explore whether 8- to 12-month-old infants associate musical rhythms they hear with synchronous visual displays by tracking their dynamic visual attention to matched and mismatched displays. Visual attention was measured using eye-tracking while they attended to a screen displaying two videos of a finger tapping at different speeds. These videos were presented side by side while infants listened to an auditory rhythm (high or low pitch) synchronized with one of the two videos. Infants attended more to the low-pitch trials than to the high-pitch trials but did not display a preference for attending to the synchronous hand over the asynchronous hand within trials. Exploratory evidence, however, suggests that tempo, pitch, and rhythmic complexity interactively engage infants’ visual attention to a tapping hand, especially when that hand is aligned with the auditory stimulus. For example, when the rhythm was complex and the auditory stimulus was low in pitch, infants attended to the fast hand more when it aligned with the auditory stream than to misaligned trials. These results suggest that the audiovisual integration in rhythmic non-speech contexts is influenced by stimulus properties.